2023
DOI: 10.1002/ncp.10967
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance analysis–derived phase angle predicts sarcopenia in patients on maintenance hemodialysis

Abstract: Background This study aimed to investigate the association between phase angle (PhA) and sarcopenia and evaluate its performance as a sarcopenia predictor in patients receveing maintenance hemodialysis (MHD). Methods All enrolled patients underwent handgrip strength (HGS) and the 6‐m walk test, and muscle mass was measured using bioelectrical impedance analysis. Sarcopenia was diagnosed according to the diagnostic criteria of the Asian Sarcopenia Working Group. Logistic regression analysis was used to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, the SMI was used to evaluate the muscle mass in patients with MHD. The phase angle is estimated based on the ratio of reactance (Xc) to resistance (R) and the formula is below: Pha (°) = arctangent (Xc / R) × (180° / π) [25] .…”
Section: Pha and Body Compositionmentioning
confidence: 99%
“…However, the SMI was used to evaluate the muscle mass in patients with MHD. The phase angle is estimated based on the ratio of reactance (Xc) to resistance (R) and the formula is below: Pha (°) = arctangent (Xc / R) × (180° / π) [25] .…”
Section: Pha and Body Compositionmentioning
confidence: 99%
“…There are diverse scores and tools to assess nutritional status, although there are no current strong recommendations. Besides clinical scales, we usually employ bioelectrical impedance analysis (BIA), a rapid, fairly cheap and non-invasive method, whose evaluation consists of a body passage of an electric current, wich gives us information about body composition and nutritional status [14][15][16][17]. By using BIA it is possible to obtain the phase angle value (PhA), which is the resistance/ reactance ratio of body tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the value, better is the nutritional status. Hence, some studies demonstrated that PhA can be used as an outcome indicator, and it is associated to mortality in dialysis patients [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation